Translating the American West into English: The Case of Hendrik Conscience's Het Goudland. - Boyden, Michael; Vandenbussche, Liselotte (Western American Literature)
This essay analyzes the US adaptations of Het Goudland (1862), an adventure novel about the California Gold Rush by the Flemish writer Hendrik Conscience (1812-1883). Contrary to other European writers of Western romances, Conscience refrained from romanticizing the West. Rather, he approached the hunt for gold as a symptom of moral decay in Belgian society at a time of intense social change. During the early 1880s, Het Goudland was adapted for an American audience in two English translations, The Boys of the Sierras (1883) and Off to California (1884). The translational changes reveal how the work was refunctionalized to fit into an emergent monolingualized vision of the West as a site of American self-realization. We argue that Conscience's novel was submitted to a threefold domesticating strategy to adjust its depiction of California and its inhabitants to an increasingly dominant Anglo-Protestant vision of the frontier: (1) the multilingualism of the original was flattened out; (2) Conscience's very negative portrayal of the West as a lawless nonplace was neutralized; and (3) the Roman-Catholic framework of the book was downplayed even while its eschatological dimension received added emphasis. Thus, the essay demonstrates that the American West as a cultural space was made not only within the borders of what is now the United States, but that this cultural construction depended in part on a selective engagement with international and multilingual traditions.